Facebook-Diagnostics: Detection of Mental Health Problems Based on Online Traces - Csepeli, György; Nagyfi, Richárd (European Journal of Mental Health, 2014)
Users of the social media network communicate with each other 24 hours a day. Their presence on Facebook leaves traces. Based on the analysis of the distribution patterns of the traces users had left, this paper aims to explore how mental states can be detected among Facebook users. Results of the analysis raise the possibility of the development of innovative methods for screening persons with mental problems among consumers and producers of online social media.